2021
DOI: 10.1186/s12874-021-01258-1
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines are needed for studies of pre-treatment HIV drug resistance: a methodological study

Abstract: Background The expansion of access to antiretroviral therapy (ART) has been accompanied by an increase in pre-treatment drug resistance (PDR). While it is critical to monitor the increasing prevalence of PDR across countries and populations to inform optimal regimen selection, the completeness of reporting is often suboptimal, limiting the interpretation and generalizability of the results. Indeed, there is no formal guidance on how studies investigating the prevalence of drug resistance should… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The survey includes 23 three-scale ordinal questions, one for each potential reporting item. These 23 items were selected in our previous methodological assessment of reporting completeness of HIV drug resistance prevalence research [ 17 ]. This list is not exhaustive, and participants are invited to add more items.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey includes 23 three-scale ordinal questions, one for each potential reporting item. These 23 items were selected in our previous methodological assessment of reporting completeness of HIV drug resistance prevalence research [ 17 ]. This list is not exhaustive, and participants are invited to add more items.…”
Section: Methodsmentioning
confidence: 99%
“…This compromises the accuracy, interpretation, and usability of prevalence estimates, especially if key data are not reported, including precision of the estimates, representativeness and diversity of the participants included, techniques used to measure resistance, participants’ transmission risk group, prior exposure to treatments, and class of drug for which resistance was tested [ 15 ]. Our recent methodological study concluded that while reporting has improved over time [ 8 ], guidance is needed to ensure complete and uniform reporting to improve the interpretation of study findings, generalizability, and comparability of prevalence estimates, while accounting for differences in geographical settings and populations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, adequate monitoring of HIV drug resistance worldwide is compromised by heterogenous and inadequate data reporting. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Despite the absence of a complete cure for the disease, research has made great advances in providing treatment regimens to mitigate the transmission of the virus. The development of antiretroviral therapies (ART), such as the highly active antiretroviral therapy (HAART), has proved to be effective in the suppression of HIV replication [ 2 ], and numerous studies have shown that the use of HIV drug resistance tests to guide therapy is associated with improved treatment outcomes [ 3 , 4 , 5 , 6 ]. The global scale-up of HAART has also dramatically decreased the rates of AIDS-related mortality and morbidity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%